Рябиновые костры: сборник стихов / Ирина Асадуллаева - Асадуллаева Ирина Александровна (РЛО "Вдохновение", 2016)
Экземпляры: УКП (20161110) / Инвентарный номер: АП20160323 / Сис.шифр: Р2 / Авт.знак: А 90 / ГРНТИ: 17.82.10 / ББК: 84(2)